(untitled) (Bangladesh Journal of Zoology, 2018)
An experiment was carried out for 6 months on rearing of common carp, mirror carp, grass carp and silver carp under polyculture system at different stocking densities in cemented tanks (5 - 7 m in diameter and water depth 1.0 - 1.5 m). Observations were made on fish growth in terms of monthly and per day weight gain. Grass carp attained the maximum weight 686 ± 17, 720 ± 16.5 and 765 ± 9.6 in three tanks, respectively. Weight gained followed by silver carp as 680 ± 10 g, 680 ± 12.6 g and 701 ± 9.2 g in tank 1, tank 2 and tank 3, respectively. The common carp gained its average maximum weight 525 ± 10.7 g in tank3 and the mirror carp also attained its maximum weight 500 ± 12.2 g in same tank. In common carp the maximum average daily weight gain (3.2 ± 0.1 g) was in the month of December and lowest was (1.92 ± 0.2 g) in the month of August in tank 3. In mirror carp the maximum average daily weight gain (3.03 ± 0.09 g) was in the month of September and lowest (1.41 ± 0.07g) in the month of July in tank 3 and tank 2, respectively. In grass carp the maximum average daily weight gain (4.24 ± 0.17 g) was in the month of August and lowest (2.72 ± 0.07 g) in the month of July in tank 3 and tank 1, respectively. Among silver carp the maximum average daily weight gain (4.45 ± 0.01 g) recorded in the month of October and lowest was (2.61 ± 0.11 g) in the month of July in tank 1. The specific growth rate (SGR) was 1.23 ± 0.64 to 1.33 ± 0.83 in common carp, 1.27 ± 0.9 to 1.34 ± 0.8 in mirror carp, 1.36 ± 0.86 to 1.55 ± 1.13 in grass carp and 1.41 ± 0.83 to 1.52 ± 1.09 in silver carp in different culture treatments. Bangladesh J. Zool. 46(1): 71-80, 2018